How chief police officers and senior loeaders from other institutions in the policing landscape in England and Wales understand the application of the concept of vulnerability to policing and its implications for police legitimacy, 2019-2021 - Shannon, Ian (UK Data Service, 2021)
The data deposited includes transcripts of six interviews with three chief police officers and three very senior leaders from other institutions in the wider policing landscape. Interviewees’ legitimating accounts based on a moral duty to use power to protect people, particularly the most vulnerable, are assessed. It is argued that the emphasis on protecting the vulnerable is new and reflects wider societal concerns, but it is also a response to a perceived need for a revised prioritisation system to cope with changed demands and previous police failings. Chief officers’ interpretations of vulnerability changed between 2016 and 2021, from predominantly strand-based understandings (located in the type of offender, offence, or victim), to stances that are more neutral about the nature of the threat, and which tend to accept the universality of vulnerability. But the ambiguity of the discourse of vulnerability, confusion about what it means, and its emotional content, may continue to be convenient for chief officers in asserting a privileged standpoint when advancing and legitimating their preferences for the use of police power and resources. This Fellowship builds on research that used semi-structured interviews to gather data to answer the question, 'how do chief police officers in England and Wales understand the right of police to exercise power?' All the chief officers interviewed invoked duties to protect the public (particularly the most vulnerable), policing by consent and explanations based in law and associated checks and balances. However, the significant academic contribution made is the finding that these accounts are confused, conflicted and, above all, convenient in helping chief police officers assert a privileged position when making decisions about the use of power. Confusion was evident in vague accounts of vulnerability and hazy notions of consensual policing. Conflict was found between a rhetoric of consent and the practice of coercion. Chief officers' claims that law and associated checks and balances are important in ensuring police power is used properly sat uncomfortably with their distaste for the process of scrutiny and they felt precarious. If police chiefs lack the confidence to resist demands for the disproportionate use of police power against those who tend to be policed more than protected, this has implications for the civil liberties of citizens. It also indicates an unhealthy relationship between police chiefs and those overseeing them, with conflict rather than constructive conversations being common. The Fellowship will be used to disseminate the findings of this research to academics, police officers and police policy makers and to those responsible for police oversight, with the intention of improving policing in the public interest. This will be done by writing a book based on the thesis, and by publishing an article on the impact of the concept of vulnerability on police practice, in the leading academic journal 'Policing and Society'. Some additional research (including six interviews) will be conducted to underpin this article and to support the discussion of vulnerability covered in the book. A further article will be written for 'Policing: A Journal of Policy and Practice', the leading practitioner-focused, academic journal. The latter article will examine the precarious position that police chief officers reported they are in and will explore the implications this has for civil liberties. The research will also be disseminated and exposed to scrutiny at international academic conferences. These publications will be supplemented by organising workshops, seminars and a symposium on police legitimacy and will be supported by a short policy focused research findings document and use of blogs. These activities will bring academics, police officers and policy makers together to discuss the implications of the research for policing practise. Using contacts and credibility developed during a policing career, latterly as a Deputy Chief Constable, and though subsequent work with the Inspectorate of Constabulary and when conducting research for the PhD, meetings will be arranged to discuss the implications of the research with Her Majesty's Chief Inspector of Constabulary, the Chief Executive Officer of the College of Policing, and the Chair of the National Police Chiefs' Council. The Fellowship will also be used to develop the skills and networks that are required for a research career. To support this collaborative work will be undertaken with other academics to explore aspects of the methodology and ethical issues dealt with during the research, notably the position of a researcher who used to be member of the group being studied. Other work will involve consideration of international studies looking at the use and abuse of police power. Full use will be made of the development opportunities that are provided for early career researchers through the Leeds Social Sciences Institute, the White Rose Doctoral Training Partnership and the N8 Policing Research Partnership, to improve my research and related skills.